Developing Public Sector Leadership - Virtanen, Petri. author. aut Link
XI, 186 p. 9 illus., 8 illus. in color.
Keywords: This book presents tools, techniques, and best practices to develop public-sector leadership. Based on scholarly research as well as the authors’ professional experience as leadership trainers and consultants, it offers guidance and practical know-how for public-sector managers, civil servants and policymakers in public administration on how to create and develop leadership skills and practice. By analyzing the particular nature of political processes and public policy decision-making as well as the complex challenges of public organizations, the authors identify competencies, leadership skills and methods required for successful governance, administration, and management of public organizations. The authors also discuss different leadership styles and philosophies, cover topics such as public sector leadership training of 2020’s, and present case studies on successful public-sector leadership development and future-oriented leadership models. Balancing public-sector leadership theory with practical illustrations and examples, tools and techniques, the book helps managers master the art of public-sector leadership.